A new surgical technique for severe ocular surface burns - Akata, Fikret; Akcam, Hanife T; Yuksel, Erdem; Yaylacioglu, Fulya (Medknow, 2022)
To describe a new surgical technique for severe ocular surface burn. A 46-year-old man suffering from bilateral sequelae of chemical injury had “allograft limbal, conjunctival, and corneal transplantation” combined with amniotic membrane transplantation and symblepharon ring implantation. The patient received mycophenolate mofetil and tacrolimus for systemic immunosuppression therapy. No intraoperative or postoperative complications were noted. After the 24 months follow-up period, the cornea was clear, and visual acuity increased from hand movement to 20/400. Allograft limbo-conjunctival-corneal transplantation (full ocular surface transplantation) might be a seminal and life-saving procedure for selected cases with severe bilateral ocular surface burn.